Fluorescent and luminescent probes for biological activity : a practical guide to technology for quantitative real-time analysis - Mason, W. T. (Biological techniques series., 1999)
The use of fluorescent and luminescent probes to measure biological function has increased dramatically since publication of the First Edition due to their improved speed, safety, and power of analytical approach. This eagerly awaited Second Edition, also edited by Bill Mason, contains 19 new chapters and over two thirds new material, and is a must for all life scientists using optical probes. The contents include discussion of new optical methodologies for detection of proteins, DNA and other molecules, as well as probes for ions, receptors, cellular components, and gene expression. Emerging and advanced technologies for probe detection such as confocal laser scanning microscopy are also covered. This book will be essential for those embarking on work in the field or using new methods to enhance their research. TOPICS COVERED: * Single and multiphoton confocal microscopy * Applications of green fluorescent protein and chemiluminescent reporters to gene expression studies * Applications of new optical probes for imaging proteins in gels * Probes and detection technologies for imaging membrane potential in live cells * Use of optical probes to detect microorganisms * Raman and confocal raman microspectroscopy * Fluorescence lifetime imaging microscopy * Digital CCD cameras and their application in biological microscopy.